Analisis dan Perancangan Sistem Informasi Manajemen Gudang pada PT Mitra Pinasthika Mulia Surabaya - Arel Riedsa Adiguna; Mochamad Chandra Saputra; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Warehouse management is managing activity of goods stored in warehouse. PT Mitra Pinasthika Mulia Surabaya is a company that applies warehouse management system to support its performance. However, PT MPM needs a new warehouse management system because, based on analyst business of PT MPM, the current warehouse management system can not support the operational activities. PT MPM cooperates with a system developer vendor to develop new warehouse management systems. In developing the system, PT MPM requires documentation system design and analysis the problems in the old system in order to arrange a system that can optimally support the company performance. Therefore, the research's goal is to analyze and design a system that can be understood by vendors and PT MPM. The design analysis was using the FAST (Framework for the Application of System Thinking) method in four phases. The first three phases produced requirement analysis with PIECES as the framework for classification of problems, while the logical design phase produce usecase, activity diagram, sequence diagram, wirefame, class diagram, CDM, and PDM. The process of design evaluation was analyzed by using consistency analysis method to prove that it has a 100% percentage value consistent and was included as the correctness category on the correctness test so the system design was concluded as consistent and correct